“Amal-I Salih” As an Important Historical Source - Azamat Ziyo (Researchparks Publishing, 2022)
Manuscripts play an important role to fill the gaps and disclose uncertain pages of history. They provide us with the information of witnesses and stories had happened prior to the author who had heard from contemporaries. Besides that, there are some manuscripts that were written by several authors and generations. The manuscript of “Amal-i Salih” is a two-volume source written by Muhammad Salih Kambu of Baburid period in India. The manuscript provides valuable information about political and diplomatic relations between Ashtarkhanids and India, information about the genealogy of the Ashtarkhanid dynasty, information about the representatives of the political, cultural, and spiritual spheres of Central Asia.